STRATEGI PROGRAM APLIKASI JUMPA MADU (JEMPUT SAMPAH TERIMA DUIT) BANK SAMPAH INDUK BERSERI TERHADAP SOSIAL EKONOMI MASYARAKAT DI KEC. LUBUK PAKAM, KABUPATEN DELI SERDANG - Jordan Joel Hiroshi Pinem; Husni Thamrin (CV. KAMPUS AKADEMIK PUBLISING, 2024)
This research aims to analyze the Strategy of the JUMPA MADU Application Program (WASTE COLLECTION, RECEIVE MONEY) at the Seri Primary Waste Bank in Lubuk Pakam District, Deli Serdang Regency, as well as the impact of this program on the socio-economic impact of the local community. The research method employed observation and interviews with key informants, primary informants, and additional informants. The results indicate that the implementation of the JUMPA MADU program requires a well-thought-out strategy, including program planning, production and purchase of the program, program execution, as well as program monitoring and evaluation. The impact of this program on the social economy of the community in Lubuk Pakam District includes increased environmental awareness, increased income through exchanging waste for money or other products, and enhanced cooperation among the community, government, and relevant institutions. This research contributes to understanding the importance of program strategy in waste management through digital applications like JUMPA MADU, and its positive impact on the social economy of the community. Recommendations from this study include the continuous development of program strategies, increasing community participation, and strengthening cooperation collaboration with related agencies to maintain the sustainability of this program in the long term.